Pipe dreams - Bowen, Sarina (A Brooklyn bruisers novel, 2017)
"Mike Beacon is a champion at defending the net, but off the ice, he's not so lucky. A widower and a single father, he's never forgotten Lauren Williams, the ex who gave him the best year of his life. When Lauren reappears in the Bruisers' office during the play-offs, Beacon sees his chance to make things right. Lauren hates that she's forced to travel with the team she used to work for and the man who broke her heart. There's still undeniable sexual tension running between her and Mike, but she won't go down that road again. She's focused on her plans for the future--she doesn't need a man to make her dreams of motherhood come true. Lauren plays her best defensive game, but she's no match for the dark-eyed goalie. When the field of play moves to Florida, things heat up on the beach. One of Mike's biggest fans doesn't approve--his teenage daughter. But a true competitor knows not to waste the perfect shot at love." -- Page [4] cover.